Two-year survival rates of anti-TNF-α therapy in psoriatic arthritis (PsA) patients with either polyarticular or oligoarticular PsA. (May 2015) - Iannone, F; Lopriore, S; Bucci, R; Scioscia, C; Anelli, MG; Notarnicola, A; Lapadula, G
<x xml:space="preserve">Abstract</x> Objectives: To evaluate the 2-year drug survival rates of the tumour necrosis factor (TNF)-α blockers adalimumab, etanercept, and infliximab in psoriatic arthritis (PsA) patients with either oligoarticular (oligo-PsA) or polyarticular PsA (poly-PsA). Method: We studied a prospective cohort of 328 PsA patients with peripheral arthritis (213 with poly-PsA and 115 with oligo-PsA), beginning their first ever anti-TNF-α treatment with adalimumab, etanercept, or infliximab. The aim of the study was to evaluate the drug survival rates and possible baseline predictors at 2 years. Results: After 24 months, persistence in therapy with the first anti-TNF-α blocker was not statistically different in the oligo-PsA (70.4%) and poly-PsA (65.7%) subsets. Predictors of drug discontinuation were female sex [hazard ratio (HR) 1.63, 95% confidence interval (CI) 1.00–2.68, p = 0.04] and starting the therapy in years 2003–8 (HR 0.51, 95% CI 0.33–0.80, p = 0.003). In poly-PsA, the persistence of etanercept (68.3%) was significantly higher than that of adalimumab (51.9%, p = 0.01), whereas in oligo-PsA no significant difference was detected. In poly-PsA, the period 2003–8 was a negative predictor (HR 0.36, 95% CI 0.21–0.62, p = 0.0001) whereas in oligo-PsA female gender was a positive predictor of drug discontinuation (HR 2.08, 95% CI 1.02–4.24, p = 0.04). With regard to clinical outcomes, the best responses in terms of European League Against Rheumatism (EULAR) 'good' response or Disease Activity Score (DAS28) remission, crude or adjusted according to the LUND Efficacy indeX (LUNDEX), were seen in patients on etanercept or infliximab. Conclusions: Our study provides some evidence that anti-TNF-α drugs may perform differently in PsA, and that the analysis of clinical disease subsets may improve our knowledge and promote better management of PsA.